Sposoby wspierania motywacji do uczenia się w alternatywnym modelu edukacji – perspektywa rodziców uczniów w młodszym wieku szkolnym - Makarewicz, Marta (Wydawnictwo Naukowe EDUsfera. Ewa Jurczyk-Romanowska, 2021)
The issue of motivation is still relevant and gain importance, especially in the context of education and the learning process. Human actions cannot exist without motivation – a state, disposition or factor that makes us choose, continue and complete the activities and tasks. The family environment is one of the most important places for young people, where we can easily find conditions responsible for a high level of motivation tolearn. Parents’ experiences in motivating their children to learn show us the important role of adults in the process of children education.
Keywords: motivation to learn; motivating to learn; selft-determination theory; parents; early school education; motivation